Impact of changes in snow cover regime on agronomic risks causing pink snow mold - K. A. Perevertin; A. I. Belolyubcev; E. A. Dronova; I. F. Asaulyak; I. A. Kuznetsov; M. A. Mazirov; T. A. Vasiliev (Лëд и снег)
Traditionally, the main strategic crop for the Russian Federation is winter cereals, therefore, the snow cover regime is of great importance for their cultivation. In the second decade of April 2021, after the snow cover disappeared on the experimental fields of Russian State Agrarian University, severe damage and partial death of winter triticale from the disease pink snow mold was noted. Measurements of the parameters of the snow cover in the period 2001–2021 showed that in the winter and spring of 2021 on the territory of Moscow the characteristics of the snow cover regime were close to agrometeorological Hazardous Phenomena standards on the territory of the Russian Federation. The risk of developing pink snow mold is directly related to the snow cover regime. Analysis of the dynamics of the characteristics of the snow cover according to the data of the Meteorological Observatory V.A. Michelson for 30 years has made it possible to propose a simple quantitative assessment of the risk of damping of winter crops. Over the past 20 years, the necessary conditions for the development of snow mold in winter cereals took place in 2010/11, 2012/13, 2017/18 and 2020/21. Analysis of the data on the early establishment of snow cover over the past 30 years shows that this factor is gradually losing its relevance due to the pronounced trend of its retardation. There is a noticeable tendency for an increase in the frequency of extremely late periods of formation of stable snow cover up to the second – third decade of January. During the study period, this phenomenon was observed in 2006 (January 20), 2013 (January 12) and 2019 (January 23). The proposed empirical function of the probability of snow cover formation, depending on the calendar date, can be recommended for assessing risks when making agronomic decisions (timing of sowing winter cereals and harvesting other crops). Freezing of crops has not been observed over the past 30 years.